AN ECONOMIC STUDY OF POST-HARVEST LOSSES FOR WHEAT FARMERS IN IRAQ BAGHDAD GOVERNORATE –CASE STUDY- - Ali, S. H.; Jabara, O. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The research aimed to measure the loss and waste of wheat farms, using exploratory and confirmatory factor analysis. Although, loss has become a frightening reality due to the loss of large quantities of food produced by humans for human consumption, so Iraq possesses material capabilities, natural resources, and human beings, it is not self-sufficient, and the reason is the low yield per dounm of wheat, as the productivity rate ranged to 650 kg / dounm for the period 1990-2019. The one of the most important reasons for the decline in productivity is the loss and waste of wheat of post- harvest. And to identify the most important factors that work to reduce post-harvest wheat losses for wheat farmers at Baghdad, by use exploratory and confirmatory factor analysis. So the results indicated that the most important factors that work to reduce losses are the duration of the crop remaining in the field after harvesting until the date of marketing it to the central silos by exposing the crop to environmental hazards, as well as attacking birds, rodents, stray animal feces, and what mixes of grains with soil. The correlation is positive and strong, at a rate of 97%, and the distance to the silo to which the crop is marketed and the logistical operations associated with it, such as crop transportation vehicles that do not comply with the conditions for the proper transportation of grains, as most of them are without cover and there are gaps and holes in them that facilitate the fall of the grains on the road is 80%, and it has a direct relationship as well. Also farmers could be increase their production without increasing economic resources by preserving wheat from loss and waste of post- harvest.